Comparison of efficacy of chlorhexidine alcohol with povidone iodine for prevention of surgical site infection: a prospective study - John, Binni; K. K., Rajith Kishore; C., Vipinchandran (International Surgery Journal, 2018)
Background: Surgical site infections (SSI’s)are the major risk factors of postoperative morbidity and mortality. The incidence of these SSI’scan be minimized by taking prophylactic measures such as using effective preoperative antiseptics such as chlorhexidine (CHG) or povidone-iodine (PVI). The aim of the present study was to compare the efficacy of 2.5% chlorhexidine-alcohol with that of 10% povidone iodine for preventing SSI’sin clean contaminated elective surgeries. Methods: This prospective study included 100 patients who were undergoing for clean contaminated elective surgeries at Government Medical College, Kottayam from April 2014 to September 2015. Group A included 50 patients in which 2.5% chlorhexidine alcohol (chlorhexidine 2.5% in 70% ethanol) was used for preoperative skin cleansing and Group B included 50 patients in which 10%povidone-iodine aqueous was used. Incidence of SSI’s in terms of efficacy was compared between the groups. Results: Female preponderance was seen in both the groups, but the difference was not significant statistically. The SSI’swere seen in 5 patients in group A and in 12 patients in group B and this difference was found statistically significant (p=0.0084).Out of 5, in group A, 3 sites were culture positive showing the presence of S. aureus culture in 1 case and E. coli in 2 cases and in group B, out of 12, 6 sites were culture positive consisting of S. aureus and E. coli in 3 cases each. Conclusions: Chlorhexidine (2.5%) significantly reduced the risk of postoperative SSIs and colonization of bacteria in elective surgeries when compared to 10% povidone iodine.